Effect of 25% Tobacco Leaf Extract (Nicotiana Tabacum L.) as a Denture Cleaning Paste on Surface Roughness and Color Change Thermoplastic Nylon - Parnaadji, Rahardyan; Naini, Amiyatun; Soesetijo, FX Ady; Kristiana, Dewi (Jurnal Riset Kesehatan, 2024)
Thermoplastic nylon as a denture base requires mechanical cleaning with denture paste. Previous research showed that tobacco leaf extract paste (TLEP) 25% was fungistatic on thermoplastic nylon denture bases. The aim is to evaluate the roughness and colour changes of thermoplastic nylon against tobacco leaf extract paste 25% during one year of simulated use. This research hypothesizes that thermoplastic nylon's roughness and colour value will decrease further after brushing using 25% TLEP. Sample groups include brushing without paste, paste without TLEP 25% and TLEP 25%. The sample size for each group was 15 samples; measurements use a surface roughness tester and a colour reader. Brushing was carried out for 23.5 minutes on a plate measuring 60x10x2.5 mm as a surface roughness test and 3.90 minutes on a plate measuring 10x10x2.5 mm as a colour change test. The sample size for each group was 15 samples; measurements use a surface roughness tester and a colour reader. The research results were tested using Kolmogorov-Smirnov and Levene and One-way ANOVA with a significance level of 0.05. There were no differences in surface roughness and colour changes on thermoplastic nylon plates after brushing with 25% TLEP (p>0.05). This study concluded that 25% TLEP did not affect increasing surface roughness and changing the colour of thermoplastic nylon plates with values below the threshold.